New research on gravity field in Lithuanian territory - Petroškevičius, Petras; Obuchovski, Romuald; Birvydienė, Rosita; Kolosovskis, Ričardas; Putrimas, Raimundas; Krikštaponis, Boleslovas; Macijauskas, Dovydas; Musteikis, Arvydas; Skuodis, Gediminas; Šorys, Tautvydas; Valotka, Simonas; Ringelevičius, Mantas; et al. (International Conference “Environmental Engineering”, 2017)
New research of Lithuanian territory gravity field was started in 2016 with aim to improve accuracy of quasigeoid as well as accuracy of normal heights determined by methods of satellite geodesy. Obtained data could be used in the research of geophysics, geodynamics as well as in performing the precise navigation. Quartz automatic gravimeters Scintrex CG are planned to be used for the survey consisting of 30000 points. Method of gravity measurements was worked out. RMS error of gravity determined with this method does not exceed 60 µGal. Coordinates and heights of measured points are determined with GNSS using LitPOS network and LIT15G quasigeoid model. RMS error of coordinate determination does not exceed 0,20 m, for normal heights – 0,15 m. Method of gravity anomalies determination and their accuracy estimation was prepared.